2019
DOI: 10.1101/740480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct features of nucleolus-associated domains in mouse embryonic stem cells

Abstract: 24Background: Heterochromatin in eukaryotic interphase cells frequently localizes to the nucleolar 25 periphery (nucleolus-associated domains, NADs) and the nuclear lamina (lamina-associated 26 domains, LADs). Gene expression in somatic cell NADs is generally low, but NADs have not 27 been characterized in mammalian stem cells. 28Results: Here, we generated the first genome-wide map of NADs in mouse embryonic stem cells 29 (mESCs) via deep sequencing of chromatin associated with biochemically-purified nucleoli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Review (Bizhanova et al, 2020;Lu et al, 2020), mouse embryonic fibroblasts (MEFs) (Vertii et al, 2019), a few human somatic cell lines (Dillinger et al, 2017;Nemeth et al, 2010;van Koningsbruggen et al, 2010), and the plant Arabidopsis thaliana (Pontvianne et al, 2016) (Table 1). Although this is the only method that until now can be used for the mapping of NADs at the genome-wide level, some limitations should be taken into consideration.…”
Section: Stem Cell Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review (Bizhanova et al, 2020;Lu et al, 2020), mouse embryonic fibroblasts (MEFs) (Vertii et al, 2019), a few human somatic cell lines (Dillinger et al, 2017;Nemeth et al, 2010;van Koningsbruggen et al, 2010), and the plant Arabidopsis thaliana (Pontvianne et al, 2016) (Table 1). Although this is the only method that until now can be used for the mapping of NADs at the genome-wide level, some limitations should be taken into consideration.…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…This discrepancy could also be due to the different methods applied for the purification of nucleoli of mESCs. Indeed, while in one work nucleoli were purified from cross-linked mESCs (Bizhanova et al, 2020), in other study this step was omitted (Lu et al, 2020). The two initial independent parallel studies that mapped NADs from biochemically purified nucleoli of HeLa, IMR90, and HT1080 human cell lines revealed that NADs contain repressive histone modifications and are enriched in olfactory receptor genes, zincfinger genes, immunoglobulin gene families, and 5S RNA genes (Nemeth et al, 2010;van Koningsbruggen et al, 2010).…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…NADs have been subdivided into type I and II NADs based on their chromatin composition and the type of LAD they correspond to [52,54]. Type-I NADs often associate with the nucleolar periphery and the lamina and contain marks of constitutive heterochromatin.…”
Section: Other 'Associated Domains'mentioning
confidence: 99%
“…Although these methods were based on completely different methodologies, they both revealed similar features of chromosome organization around the nucleolus in ESCs and NPCs. Previous methods for NAD identification used sonication-based biochemical purification of nucleoli, a methodology that is subjected to a certain variation in nucleoli preparation between different cell types and relatively biased toward sonication-resistant heterochromatin (Bizhanova et al, 2020; Dillinger et al, 2017; Lu et al, 2020; Nemeth et al, 2010; van Koningsbruggen et al, 2010; Vertii et al, 2019). Relative to this methodology, the application of Nucleolar-DamID and HiC-rDNA has no bias for any kind of chromatin state and does not vary between cell types, thereby allowing direct comparisons of chromosome architecture around the nucleolus between distinct cell states.…”
Section: Discussionmentioning
confidence: 99%
“…First, since the heterochromatin is generally resistant to sonication (Becker et al, 2017), the identification of NADs upon sequencing of nucleoli purified through sonication can be biased toward repressive chromatin domains. Secondly, the experimental procedures to isolate nucleoli can be subjected to a certain variation, generating highly divergent NAD maps, even from the same cell types (Bizhanova et al, 2020; Lu et al, 2020). Third, it is difficult to achieve the purification of nucleoli in cells with open genome, such as embryonic stem cells (ESCs), unless protein-DNA crosslinking reagents are used, with a consequent extension of sonication time.…”
Section: Introductionmentioning
confidence: 99%